Kompresor Angin Terintegrasi Berbasis Mikrokontrol PIC 16F877 Dengan User Interface VB 6.0 - ., Sugeng; ., Waluyo (Program Studi Teknik Elektro Fakultas Teknik Universitas Islam 45 Bekasi, 2012)
Integrated air compressor is a system to integrate some air compressor become one unity which is supporting each other. In this system used microcontrol PIC 16F877 as compressor hardware controller and VB 6.0 as interface between compressor and user. Integrated air compressor to be designed as solution problems of arising out at conventional compressor system with damage storey level which enough high as effect of over loading, over running and over themperature. Result of test from prototype show that the design tool is good relation between compressor one with other in a integrity which each other to backup when failure execute and also not good in performance, so that this system enough effective to depressing its damage of compressor as effect of over loading, over themperature and overrunning.